Desenvolvimento de método voltamétrico para a determinação simultânea de pesticidas em água utilizando eletrodo compósito - Silva, Gleiciane Barros Ferreira da (2020)
This work describes the development and validation of the electroanalytical method for quantification of the pesticides carbendazim (CBZ), diuron (DI) and carbofuran (CF) in surface water, using a composite electrode (EC) based on graphite and polycaprolactone (PCL) with and without modification with gold nanoparticles (AuNPs). The ECs were made in the proportion of 70% (mass of graphite), and the modified EC incorporated 5% of AuNPs anchored in Carbon Vulcan, in the proportion of 25:45:30 (% m) (AuNPs/C:Graphite:PCL) , maintaining the proportion of 70% in carbonaceous material in the composite. The analytical application of ECs was evaluated for the individual and simultaneous determination of pesticides. For CBZ, a quasi-reversible oxidation peak was observed at +0.76 V, while for DI and CF an irreversible oxidation peak at +0.88 V and +1.32 V vs. Ag/AgCl, respectively, in 0.1 mol L-1 phosphate buffer (pH 7.0), characterized by diffusion-controlled processes. The instrumental parameters of differential pulse voltammetry have been optimized, with the best response in terms of sensitivity and selectivity obtained by applying pulse amplitude (△Ep) of 50 mV, potential increase (Es) of 5 mV and pulse time (tp) of 0.2s. The modification of EC with AuNPs did not result in improved sensitivity in the response to pesticides. However, it was observed that the response to EC when compared to the glassy carbon electrode showed a higher signal intensity for the simultaneous determination of pesticides. The simultaneous analytical curve was obtained in the concentration range of 10 to 105 µg L1 (R2 = 0.9967) for CBZ and 100 to 1059 µg L-1 (R2 = 0.9979) for DI and from 4.0 to 43.0 mg L-1 (R2 = 0.9993) for CF, with detection limits (LD) of 4.0 µgL-1 , 35.0 µg L-1 and 1.0 mg L-1 for CBZ, DI and CF respectively. For the binary analysis of CBZ and DI a concentration range of 5 to 105 µg L-1 (R2 = 0.9987) was obtained for CBZ and 50 to 1059 µg L-1 (R2 = 0.9934) for DI, with lower detection and quantification limits reached of 18.0 µg L-1 and 55.0 µg L-1 for DI, with DPR less than 5%. The proposed method was applied for simultaneous determination of pesticides in fortified surface water samples without the need for any type of sample pretreatment, with recoveries between 78.0 to 88.8% for CBZ and between 79.4 to 105.5% for DI, and showed no significant differences with the reference chromatographic method at a 95% confidence level, demonstrating the applicability of the method.